THE INFLUANCE OF FINANCIAL BEHAVIOR, FINANCIAL LITERACY, AND FINANCIAL TECHNOLOGY ON THE PERFOMANCE OF MSMEs IN MATARAM CITY - Natasha, Octavia; Hilendri, Baiq Anggun; Agustiningsih, Wulandari (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2024)
The research analyze influence of financial behavior, financial literacy, and financial technology on the performance of Mataram City MSMEs. The method used is a quantitative approach with surveys as a data collection technique. The population of this research is MSME actors who own MSME businesses in Mataram City, with a sample taken randomly of 100 respondents. The collected data was analyzed using multiple linear regression to test the relationship between variables. Temun shows that financial behavior has no significant effect on the performance of MSMEs in Mataram City, financial literacy has no effect on the performance of Mataram City, and financial technology has a positive influence on the performance of MSMEs in Mataram City. The results of this research emphasize the importance of strengthening financial behavior, financial literacy and financial technology to support MSME performance and better economic growth.